Cytogenetical Study of a Multifocal Uveal Melanoma. (May 2014) - Filloy, Alejandro; Caminal, J. Maria; Bruzual, Maria C.; Varela, Maria del M.; Gomà, Montserrat
Abstract Choroidal melanoma may arise de novo or transformed from a previously existing nevus. Modern cytogenetical techniques allow us to determine and classify the genetic aberrations of such tumors. We report a case of a 55-year-old man presenting a malignant transformation of a previously known choroidal nevus in his right eye. Nine years earlier, that same eye was treated with brachytherapy for a malignant melanoma. Enucleation was indicated followed by histopathological study as well as gene mutation analysis of the tumor cells. The second melanoma was anatomically independent from the first one, discarding the possibility of spreading. Cytogenetical study resulted in significant loss of the short arm of chromosome 1 and the long arm of chromosome 3. Only 21 cases of multiple uveal melanoma in the same eye are reported in the literature. To our knowledge this is the first cytogenetical report of one of such cases. It highlights the importance of follow-up in these patients, especially when risk factors like a choroidal naevus are present.